2006
DOI: 10.1097/01.yco.0000228768.79097.3e
|View full text |Cite
|
Sign up to set email alerts
|

Medical complications of anorexia nervosa and bulimia nervosa

Abstract: Medical complications are common and often serious in patients with eating disorders, particularly those with anorexia nervosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
225
1
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 373 publications
(238 citation statements)
references
References 40 publications
6
225
1
6
Order By: Relevance
“…(Jacobs et al, 2012;Liederbach & Compagno, 2001;Wentz et al, 2012) Energy deficiency and disordered eating that may lead to medical complications on the musculoskeletal system, such as osteopenia/osteoporosis and myopathy. (Mitchell & Crow, 2006) Furthermore, functional impairments associated with low energy availability include a greater prevalence of injuries (Thein-Nissenbaum et al, 2011) and this can explain why such instructors are at higher risk of both injuries and musculoskeletal pain. Although menstrual dysfunction was not associated with injuries among respondents in this study, a significant number of both LIL and HIL female instructors reported such dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…(Jacobs et al, 2012;Liederbach & Compagno, 2001;Wentz et al, 2012) Energy deficiency and disordered eating that may lead to medical complications on the musculoskeletal system, such as osteopenia/osteoporosis and myopathy. (Mitchell & Crow, 2006) Furthermore, functional impairments associated with low energy availability include a greater prevalence of injuries (Thein-Nissenbaum et al, 2011) and this can explain why such instructors are at higher risk of both injuries and musculoskeletal pain. Although menstrual dysfunction was not associated with injuries among respondents in this study, a significant number of both LIL and HIL female instructors reported such dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized comparison Eating disorders (EDs) are associated with a wide range of medical complications involving all major systems of the body (Kaplan & Woodside, 1987;Mitchell & Crow, 2006), and in severe cases EDs may lead to death (Herzog et al, 2000). Further, even the most empirically supported treatment for eating disorders (i.e., cognitive behavioral therapy for bulimia nervosa) is only effective for about 60% of those completing treatment (Fairburn et al, 1995).…”
mentioning
confidence: 99%
“…Eating disorders particularly anorexia nervosa is reported to disrupt several system with resultant complications of metabolic diseases. Particularly, anorectic patients have been reported to die at a premature age possibly from medical complications [27]. This disconcerting information should come in the knowledge of such individuals suffering from the disorder or at a high risk of developing one, who involve grossly in unhealthy dieting particularly females.…”
Section: Discussionmentioning
confidence: 99%